The Effect of Self-Efficacy on the Writing Ability of English Study Program Students at IAIN Palangka Raya - Hakikiy, Nur; Siminto, Siminto; Qamariah, Zaitun (Journal of English Language and Education, 2025)
In learning English as a foreign language, four skills should be mastered by the learners. They are listening, speaking, reading, and writing. Writing has an important role for people. Writing is one of the ways to communicate as well as speaking. Some people my not like it much, because in general, writing skills are rarely more favorite than other. After all, it includes many aspects such as vocabulary, grammar, idioms, and so on. Writing is also the most important skill you need in University. It will be helpful when we need to accomplish our theses.  Self-efficacy, an individual's belief in his or her ability to achieve certain goals, is considered an important factor influencing academic performance, including writing skills. This study involved 48 Semester 6th students from the English language education study program at the Palangka Raya State Islamic Institute, using a self-efficacy questionnaire and a writing test as instruments. Data were analyzed using Pearson Product Moment Correlation to determine the strength and direction of the relationship between the two variables. From the results of the data analysis, it is clear that there is a relationship between self-efficacy (variable X) and writing ability (variable Y). The correlation results show that the value of r = 0.2053 is included in the "Weak" category, which indicates that although there is a positive correlation between Student Self-Efficacy and Writing Ability, this relationship is not strong. The coefficient of determination R² = 0.0422 or 4.22% indicates that only a small part of the variation in writing ability can be explained by student self-efficacy. T-test: The calculated t-value is 1.42. With a sample size of n = 48 and a commonly used significance level (α = 0.05), this t-value is not significant. This means there is no strong evidence to conclude that there is a significant relationship between self-efficacy and writing ability in this sample. The results of this study expand the understanding of the importance of other factors such as motivation, learning environment, and social support that may have more influence on improving writing skills. The study also confirms that the development of writing skills requires a holistic approach, which includes not only improving self-efficacy but also other aspects of the learning process.